(untitled) (Global Journal of Medical Research, 2019)
Early detection of markers of joint damage in order to predict the course of the inflammatory process and the risk of developing post-traumatic osteoarthritis is one of the urgent problems of traumatology and orthopedics. Determining the molecules of average mass and necrotic substances in the hemosynovial fluid of the injured knee joint demonstrates a significant association with the severity of the injury, the severity of the inflammatory process and the progression of post-traumatic osteoarthritis. Increasing the level of necrotic substances in hemosynovial fluid to 1.6-2.0 U/ml, 45.4% corresponds to significant damage to the intra-articular structures and leads to the development of the inflammatory process; an increase in excess of 2.0 U/ml is an indicator of severe joint injury and leads to a complicated postoperative course.